Chirality enriched carbon nanotubes with tunable wrapping via corona phase exchange purification (CPEP). Issue 23 (31st May 2019) - Nißler, Robert; Mann, Florian A.; Preiß, Helen; Selvaggio, Gabriele; Herrmann, Niklas; Kruss, Sebastian
Abstract : A novel process (CPEP) for chirality enriched single-walled carbon nanotubes with tunable functionalization. Abstract : Single-walled carbon nanotubes (SWCNTs) have unique photophysical properties and serve as building blocks for biosensors, functional materials and devices. For many applications it is crucial to use chirality-pure SWCNTs, which requires sophisticated processes. Purification procedures such as wrapping by certain polymers, phase separation, density gradient centrifugation or gel chromatography have been developed and yield distinct SWCNT species wrapped by a specific polymer or surfactant. However, many applications require a different organic functionalization (corona) around the SWCNTs instead of the one used for the purification process. Here, we present a novel efficient and straightforward process to gain chirality pure SWCNTs with tunable functionalization. Our approach uses polyfluorene (PFO) polymers to enrich certain chiralities but the polymer is removed again and finally exchanged to any desired organic phase. We demonstrate this concept by dispersing SWCNTs in poly[(9, 9-dioctylfluorenyl-2, 7-diyl)- alt-co -(6, 6′-{2, 2′-bipyridine})] (PFO-BPy), which is known to preferentially solubilize (6, 5)-SWCNTs. Then PFO-BPy is removed and recycled, while letting the SWCNTs adsorb/agglomerate on sodium chloride (NaCl) crystals, which act as a toluene-stable but water-soluble filler material. In the last step these purified SWCNTs are redispersed in different polymers, surfactants and ssDNA. This corona phase exchange purification (CPEP) approach was also extended to other PFO variants to enrich and functionalize (7, 5)-SWCNTs. CPEP purified and functionalized SWCNTs display monodisperse nIR spectra, which are important for fundamental studies and applications that rely on spectral changes. We show this advantage for SWCNT-based nIR fluorescent sensors for the neurotransmitter dopamine and red-shifted sp 3 defect peaks . In summary, CPEP makes use of PFO polymers for chirality enrichment but provides access to chirality enriched SWCNTs functionalized in any desired polymer, surfactant or biopolymer.